Taiga penguins: expressing existence and finctionality in a phenomenon-based classification - Claudio Gnoli; Patrícia de Almeida; Luís Miguel Oliveira Machado; Riccardo Ridi (Ergon, 2022)
The Integrative Levels Classification (ILC) lists phenomena of the real world rather than disciplines. This poses various challenges to represent in ILC fictional, hypothetical or metaphysical entities that are not listed among ordinary “phenomena”. One device to address this are ILC deictic classes for “reality/being”, “the present” and “the existent”. Their codes can be used either alone or attached to a class of phenomena, to express e.g. actual horses as opposed to horses in general. Some faceted combinations may stand for non-existent entities, like “taiga penguins” or “winged horses”. Fictional entities can be expressed by such combinations without an existence deictic. The representation of spiritual entities like divinities or demons may involve both deictics and classes defined at the cultural level, also depending on the metaphysical assumptions of the classification system. Some solutions as well as open problems are discussed with examples from ILC notation.